1956
DOI: 10.1139/v56-057
|View full text |Cite
|
Sign up to set email alerts
|

CROSS-LINKING OF COPOLYMERS FROM METHYL VINYL KETONE AND n-BUTYL ACRYLATE

Abstract: Copolymers of n-butyl acrylate and methyl vinyl ketone can be cross-linked by a combination of sulphur and zinc oxide; the reaction is associated with the methyl vinyl ltetone units in the polyn~er chain. From studies on the copolymers and model conlpounds, it is suggested that adjacent pairs or groups of methyl vinyl ketone units in the polymer cyclize t o give ap ~~n s a t u r a t e d ltetone groups. These contain reactive hydrogen which is attacked by sulphur; disulphide or zinc mercaptide cross-linlts are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1958
1958
1999
1999

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Cooper and Catterall (87) reported that copolymers of n-butylacrylate and methyl vinyl ketone could be cross-linked by a combination of sulfur and zinc oxide. It was postulated that disulfide cross-linkages…”
Section: Free-radical Copolymerizationmentioning
confidence: 99%
“…Cooper and Catterall (87) reported that copolymers of n-butylacrylate and methyl vinyl ketone could be cross-linked by a combination of sulfur and zinc oxide. It was postulated that disulfide cross-linkages…”
Section: Free-radical Copolymerizationmentioning
confidence: 99%
“…Many difficulties could be overcome by cross linking the ester copolymers directly with basic oxides or hydroxides. The use of such compounds for cross linking polyacrylates is known (7,7,9,12), and they would be expected to be equally effective for butadiene-acrylate copolymers.…”
mentioning
confidence: 99%